(untitled) (Research, Society and Development, 2022)
Objective: to track the variables necessary for a database of ostomy patients in health services. The guiding question was established: What are the necessary variables for a database of patients with ostomy in health services?. Method: This is a scope review protocol, based on the Joanna Briggs Institute manual and checklist Prefered Reporing Items for Systematic Review and Meta-Analyses - Extension for Scoping Reviews. A search will be carried out in the literature using descriptors from Health Science and Medical Subject Headings. The selection of studies will be made by two researchers independently. For the interpretation of the results, the IRaMuTeQ software will be used. The data obtained will be organized in flowcharts, infographics and, if applicable, tables and graphs that facilitate the presentation of the results. A summary will also be presented to be elaborated in a narrative form from the variables that arise.